9. ULTRASOUND-ASSISTED SPINAL ANESTHESIA AT L5-S1 IN PATIENTS WITH ANKYLOSING SPONDYLITIS (Vietnam Journal of Community Medicine, 2024)
Background: Spinal anesthesia in patients with ankylosing spondylitis is a challenge for anesthesiologists. Spinal anesthesia at the L5-S1 interspace was described by Taylor in 1940 and was proven to be effective and safe. We evaluate the effectiveness and the side effects of ultrasound-assisted spinal anesthesia at L5-S1 in patients with ankylosing spondylitis.Methods: Descriptive study on 16 patients with ankylosing spondylitis.Results: L5-S1 interspace was seen in all patients on paramedian sagittal oblique view and in 7 patients (43.75%) on transverse interlaminar view. The time taken to identify landmarks was 153.56 ± 68.37 seconds, time taken to administer spinal anesthesia was 81.88 ± 14.17 seconds. Successful dural puncture at the first attempt in all patients. The maximum number of needle directions is 3 times, 6 patients did not need to change the needle direction during perform spinal anesthesia. The highest level of sensory block after 25 minutes was T4, and the lowest level of sensory block was T11. All patients in our study had complete loss of movement in the operated limb. Side effects: itching in 2 patients, vomiting and nausea in 1 patient, and shivering in 1 patient. No patient had hypotension during spinal anesthesia and surgery.Conclusions: Spinal anesthesia in patients with ankylosing spondylitis can be performed safely and effectively with ultrasound-assisted.
Keywords: Ankylosing spondylitis; ultrasound-assisted spinal anesthesia